Contemporary music tourism : a theory of musical topophilia - Bolderman, Leonieke, 1985- (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This book explores the growing phenomenon of music tourism - instances of people visiting places because of a connection with music. Asking how an abstract art form such as music can lead to tourism and how the popularity of music tourism in contemporary culture might be explained, it presents a comparative study of music tourism in various locations across Europe, in relation to a range of musical genres. Through the concept of 'musical topophilia', the author offers a timely and insightful analysis of the affective attachment to place and music, showing how and why music literally moves people. This account enables us to grasp the complex ways in which music, place and tourism are connected in practice. Based on empirical case studies, Contemporary Music Tourism lays the foundation for a theoretical grounding of music tourism as a research field and as such, will appeal to scholars of geography, music, sociology, tourism, and cultural studies and music"--
Music, place and tourism -- Musical topophilia -- Sharing songs on Hirakata Square. On music listening and imagining place Have you found what you're looking for? Music tourists, experience and identity -- There is just such a mental buzz! Music workshops, place and belonging -- The value of music tourism.
OCLC-licensed vendor bibliographic record.
Keywords: Music and tourism; Music -- Social aspects; SOCIAL SCIENCE / Sociology / General